2017
DOI: 10.4103/jrpp.jrpp_16_163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the interaction of intravenous and oral voriconazole with oral cyclosporine in iranian HSCT patients

Abstract: Objective:Voriconazole as a triazole antifungal agent is widely used for prophylaxis or treatment of fungal infections in allogeneic hematopoietic stem cell transplantation (HSCT). It can increase blood concentrations of other medications including cyclosporine A (CsA) which are substrates for cytochrome P450 3A4. The aim of this study was to evaluate comparatively the interaction between oral/intravenous (IV) voriconazole and oral CsA.Methods:Twenty-nine recipients of allogeneic HSCT who had been already on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Tis is because it impacts whether it is necessary to preemptively reduce the dosage of CsA according to the instructions when coadministered with triazole antifungal drugs in patients with diferent diseases. Hamidreza et al [26] found that the mean C/D ratio of CsA increased 8.40%-174.10% when co-administered with VCZ in patients received HSCT. POSA increased the mean C/D ratio of CsA to a similar extent in patients with aplastic anaemia in current study (7.60%-184.00%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis is because it impacts whether it is necessary to preemptively reduce the dosage of CsA according to the instructions when coadministered with triazole antifungal drugs in patients with diferent diseases. Hamidreza et al [26] found that the mean C/D ratio of CsA increased 8.40%-174.10% when co-administered with VCZ in patients received HSCT. POSA increased the mean C/D ratio of CsA to a similar extent in patients with aplastic anaemia in current study (7.60%-184.00%).…”
Section: Discussionmentioning
confidence: 99%
“…Sanchez-Ortega et al [20] suggested that reducing the CsA dose may lead to a subtherapeutic CsA concentration, thus afecting the therapeutic efect. Hadjibabaie et al [26] suggested avoiding uniform reduction in all patients before voriconazole administration, and recommend frequent CsA blood concentration monitoring, once voriconazole antifungal therapy is initiated. In addition, a study also indicated that the dose adjustment of CsA inhibitors for initiating azoles should not be decided uniformly but should be determined individually by closely monitoring their blood concentrations [31].…”
Section: Discussionmentioning
confidence: 99%
“…Masoumi et al found that starting voriconazole increased the ciclosporin blood level to administered dose ratio from 8.4% to 174.1%. It is noted that patient-based factors may play an important role in this wide range of occurrences 22. Posaconazole, another interacting drug, is shown to be an important cause of increased ciclosporin blood levels.…”
Section: Discussionmentioning
confidence: 99%